ChemInform Abstract: 4, 5‐seco‐Probotryenols A—C, a New Type of Sesquiterpenoids from Stachybotrys bisbyi. Issue 39 (September 2015) - Chen, Guo‐Dong; et al.
Abstract [isolation, structure elucidation and cytotoxicity of three new seco‐probotryane‐type sesquiterpenoids, 4, 5‐seco‐probotryenols A‐C (I), along with five new botryane sesquiterpenoids, i.e.